PENINGKATAN PEMANFAATAN E-COMMERCE SEBAGAI UPAYA PENGEMBANGAN USAHA MIKRO, KECIL, DAN MENENGAH DALAM PROGRAM KKNT-MBKM DI KELURAHAN RUNGKUT TENGAH, KECAMATAN GUNUNG ANYAR, KOTA SURABAYA - Rohman, Muhammad Handi; Taufiq, M.; Wijaya, Riko Setya (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
This journal aims to discuss the importance of utilizing e-commerce in the development of micro, small, and medium enterprises (MSMEs) in the KKN program. E-commerce has become a global phenomenon that allows businesses to reach a wider market and improve their operational efficiency. However, there are still many MSMEs that have not maximized the potential of e-commerce. Therefore, this study was conducted to analyze the factors that influence the use of e-commerce by MSMEs and the strategies that can be implemented in the KKN program to increase the use of e-commerce by MSMEs. The research methods used in this journal are literature studies and case studies. Literature studies were conducted to gain a comprehensive understanding of the concept of e-commerce, its benefits for MSMEs, and the factors that influence its utilization. In addition, case studies were conducted involving a number of MSMEs participating in the KKN program. Data was collected through interviews and observations of these MSMEs. The results showed that factors such as limited access to technology, lack of knowledge and skills about e-commerce, and security and privacy concerns are some of the major barriers to the utilization of e-commerce by MSMEs. Therefore, the recommended strategies in the SCS program include providing training and mentoring for MSMEs in e-commerce utilization, developing more affordable and accessible technology infrastructure, and raising awareness about the benefits of e-commerce and data protection measures. This journal is expected to provide a better understanding of the importance of e-commerce utilization in the development of MSMEs in the SCS program. By implementing the suggested strategies, it is expected that MSMEs can improve their operational efficiency, reach a wider market, and contribute to local economic growth. Keywords: E-commerce, micro, small and medium enterprises, KKN, training, technology infrastructure